Recommendations for remote observation of caregiver-infant feeding interactions via virtual home visits - Ventura, Alison K.; Rossi, Alondra; Ryder, Molly M.; Thomas, Gabriella M.; Eaddy, Sammy; Ceja Almontes, Karla I.; Diaz, Cynthia L. (Frontiers in Developmental Psychology, 2025)
Observational studies of caregiver-infant feeding interactions are necessary for understanding early relational dynamics, infant behavior, and developmental trajectories. However, traditional in-person observation methods pose logistical and access-related barriers, particularly for families with limited resources. In this article, we provide a comprehensive guide for conducting remote observations of caregiver-infant feeding interactions using virtual home visits, with a focus on feasibility, equity, and data quality. Drawing on recent technological advances and lessons from implementation, we outline practical strategies for scheduling, participant preparation, technology setup, and researcher management of virtual visits. We also address common challenges related to video quality, audio fidelity, camera framing, internet connectivity, and environmental distractions. Recommendations include using common videoconferencing platforms (e.g., Zoom), piloting device setup, minimizing participant burden, using scripting to reduce bias, and actively managing technical limitations. When implemented thoughtfully, remote protocols can yield high-quality, ecologically valid data across diverse populations, making remote caregiver-infant feeding observations a viable alternative to in-person assessments. This article offers researchers and clinicians an adaptable framework for conducting reliable, accessible, and family-centered virtual feeding observations.